Une agence à l’œuvre du Paris haussmannien : l’agence d’Henri Blondel (1821-1897) - Elsa Jamet (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
By the end of the 19th century, the architecture agency run by Henri Blondel (1821-1897) was one of the leading agencies in Paris. Active from 1852 to 1894, he contributed to the construction of the new Haussmannian Paris. The days of his agency were thus punctuated by drilling and aligning new roads, as well as building housing estates and rental houses.To support him in this task, many architectural auditors, assistants, experts and engineers worked for him in his offices at 14 quai de la Mégisserie in Paris. These business affairs were supported by the Prefect of the Seine, Georges-Eugène Haussmann, to whom Blondel was close.Having speculated financially throughout his career, Blondel was soon forgotten after filing bankruptcy for more than 25 million francs in liabilities. A certain number of unpublished source materials, however, allow us to study the agency’s organization along with the entirety of its activities throughout its existence.